2011
DOI: 10.4028/www.scientific.net/amr.189-193.805
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Corrosion Studies of Amorphous/Nanocrystalline Conversion Coatings Formed by Applying Static Magnetic Field on AZ91 D Magnesium Alloy

Abstract: The present work explores an environmental friendly method for forming conversion coatings on AZ91D magnesium alloy by applying a static magnetic field. An amorphous / nanocrystalline conversion coating was developed on magnesium alloys in a phosphate-permanganate aqueous solution under a 0.5 Tesla magnetic field. The examinations of the microstructure and phase compositions reveal that the conversion coating is composed of an amorphous structure and nanocrystalline structure with mean size less than 10 nm. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…86 Moreover, the utility of a magnetic eld as a control measure in certain chemical conversion processes has been investigated. Some researchers [97][98][99][100] have reported that the application of an external magnetic eld could improve the quality of chemical conversion coatings because there is strong, localized convection arising from the micro magnetohydrodynamic effect. Briey, this method can not only improve the dispersion of nanoparticles, but also benet the quality of matrix coatings and is therefore considered to be a promising approach.…”
Section: Magnetic Eldmentioning
confidence: 99%
“…86 Moreover, the utility of a magnetic eld as a control measure in certain chemical conversion processes has been investigated. Some researchers [97][98][99][100] have reported that the application of an external magnetic eld could improve the quality of chemical conversion coatings because there is strong, localized convection arising from the micro magnetohydrodynamic effect. Briey, this method can not only improve the dispersion of nanoparticles, but also benet the quality of matrix coatings and is therefore considered to be a promising approach.…”
Section: Magnetic Eldmentioning
confidence: 99%